Genistein Suppresses IL-6 and MMP-13 to Attenuate Osteoarthritis in Obese Diabetic Mice - Janelle Lopez; Layla Al-Nakkash; Tom L. Broderick; Monica Castro; Brielle Tobin; Jeffrey H. Plochocki (Metabolites, 2023)
Type 2 diabetes mellitus and osteoarthritis (OA) often present as comorbidities. We examined the role of plasma IL-6, chondrocyte MMP-13, and col10a expression in the development of OA in obese diabetic mice. We further investigated dietary genistein and exercise training as potential mitigators of OA. One hundred adult mice (50 females, 50 males) aged 6 weeks were randomized into 5 groups, including lean controls, obese diabetic controls, and obese diabetic mice treated with genistein, exercise training, and genistein plus exercise training. The obese diabetic state was induced by feeding the mice a high-fat, high-sugar diet. Genistein was incorporated into the diet at a concentration of 600 mg genistein/kg. Exercise training was performed on a treadmill and consisted of daily 30 min sessions at 12 m/min, 5 days/week for a 12-week period. After treatment, plasma was collected, and proximal tibias were removed for analysis. Plasma IL-6 and MMP-13 were elevated while col10a was reduced in obese diabetic mice in comparison to lean controls. Dietary genistein treatment reduced IL-6 and MMP-13 expression and increased col10a expression. Histological examination of articular cartilage showed reduced thickness of the uncalcified zones and proteoglycan content in the cartilage of diabetic mice in comparison to mice fed genistein. Exercise training had no significant effect. In conclusion, genistein (and not exercise training) attenuates OA by reducing IL-6 and MMP-13 expression in diabetic mice.